Case report: Renal malformations in wild roe deer (Capreolus capreolus) in Central Poland - Kliczkowska, Katarzyna; Bielecki, Wojciech; Kloch, Marta; Świątek, Marcin; Klich, Daniel (Frontiers in Veterinary Science, 2025)
Kidney diseases are observed in various wild animal species, more often noted in captive than in free-ranging animals. There are few reports in roe deer (Capreolus capreolus). Two kidney malformations were encountered while reviewing and collecting the roe deer samples. Kidney malformations were found in samples from two roe deer in Central Poland, one in 5-year-old female near Węgrów (50 km northeast of Warsaw) and one in 7-year-old male near Rawa Mazowiecka (75 km southwest of Warsaw). The female had a smaller (5 cm long and weighed 20 g) shrunken kidney (no prominent histopathological changes) and compensatory hypertrophy of the other kidney (weighting 85.8 g). A diagnosis of renal hypoplasia was made. The male had a smaller kidney (4.5 cm long and weighed 15.3 g) and normal-sized the other kidney (7.5 cm and 55.6 g). Massive mononuclear infiltrates composed mainly of lymphocytes and plasma cells in the renal interstitium, with hyperplasia of the connective tissue and multifocal glomerular sclerosis, were found in both kidneys. Diagnosis of chronic interstitial nephritis was made.